Cinema, history and technique. A comparison between the oral narration and cinematographic narrative of history from the films Violeta se fue a los cielos and Sub-Terra - Kuhlmann Fehlandt, Carolina (Re-presentaciones: Periodismo, comunicación y sociedad, 2018)
The present work studies the articulation between cinema, history and technique, in the context of historical representations produced by Chilean fiction cinema. To undertake such a task, a comparison is made between two mnemonics: the cinematographic narrative and the oral narration of history. The comparative study materializes in the analysis of two Chilean films that, on one hand, narrate a historical theme, and, on the other, present a content related to oral narration. These films are Violeta se fue a los cielos (2011) and Sub-Terra (2003).